The Effect Of Institutional Ownership, Profitability, Financial Leverage, And Free Cash Flow On Earnings Management In Mining Companies Listed On The Indonesia Stock Exchange (IDX) For The 2019-2023 Period - Aurellia Zandrafitria; M. Irfan Tarmizi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Earnings reports are an important component of financial reports, but are often manipulated for certain interests. This study aims to examine the effect of institutional ownership, profitability, financial leverage, and free cash flow on earnings management in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The study used a quantitative descriptive method with secondary data in the form of annual financial reports which were analyzed using panel data regression through Eviews 12 software. The results showed that institutional ownership and financial leverage had no significant effect on earnings management. Profitability has a significant negative effect, while free cash flow has a significant positive effect on earnings management. These findings partially support agency theory and reinforce the importance of effective supervisory mechanisms in preventing earnings manipulation practices. This research is expected to provide theoretical and practical insights for stakeholders and become a reference for further research